Discovery of a Highly Conserved Peptide in the Iron Transporter Melanotransferrin that Traverses an Intact Blood Brain Barrier and Localizes in Neural Cells - Singh, Chaahat S. B.; Eyford, Brett A.; Abraham, Thomas; Munro, Lonna; Choi, Kyung Bok; Okon, Mark; Vitalis, Timothy Z.; Gabathuler, Reinhard; Lu, Chieh-Ju; Pfeifer, Cheryl G.; Tian, Mei Mei; Jefferies, Wilfred A. (Frontiers in Neuroscience, 2021)
The blood-brain barrier (BBB) hinders the distribution of therapeutics intended for treatment of diseases of the brain. Our previous studies showed that that a soluble form of melanotransferrin (MTf; Uniprot P08582; also known as p97, MFI2 and CD228), a mammalian iron-transport protein, is an effective carrier for delivery of drug conjugates across the BBB into the brain and was the first BBB targeting delivery system to demonstrate therapeutic efficacy within the brain. Here, we performed a screen to identify peptides from MTf capable of traversing the BBB. We identified a highly conserved twelve-amino acid peptide, termed MTfp, that retains the ability to cross the intact BBB intact and enter intacellular organelles within neurons, glia and microglia in the brain. This peptide may provide a platform for the transport of therapeutics to the CNS, and thereby offers new avenues for potential treatments of neuropathologies that are currently refractory to existing therapies.